Effect of free running wheel exercise on renal expression of parathyroid hormone receptor type 1 in spontaneously hypertensive rats - Braun, Katja; Atmanspacher, Felix; Schreckenberg, Rolf; Grgic, Ivica; Schlüter, Klaus-Dieter; Justus Liebig University Giessen (My University, 2018)
An active lifestyle is generally recommended for hypertensive patients to prevent subsequent end-organ damage. However, experimental data on long-term effects of exercise on hypertension are insufficient and underlying mechanisms are not well understood. This study was aimed to investigate the effect of exercise on renal expression of parathyroid hormone-related protein (PTHrP) and parathyroid hormone receptor type 1 (PTHR1) in spontaneously hypertensive rats (SHR). Twenty-four rats started free running wheel exercise at the age of 1.5 months (pre-hypertensive state) and proceeded for 1.5, 3.0, 6.0, and 10.0 months. Thirty rats kept under standard housing conditions were used as sedentary controls. Kidney function was assessed by measuring plasma creatinine levels and urine albumin-to-creatinine ratios. Renal expression of PTHrP and PTHR1 was analyzed by qRT-PCR and western blot. Renal expression of PTHR1 was markedly increased between the 6th and 10th months in sedentary rats and this increase was significantly lower in SHRs with high physical activity on mRNA (-30%) and protein level (-27%). At the same time, urine albumin-to-creatinine ratio increased (from 65 to 231 mg/g) but somehow lower in exercise performing SHRs (48 196 mg/g). Our data suggest that enhanced exercise, stimulated by allocation of a free running wheel, is associated with lower PTHR1 expression in SHRs and this may contribute to preserved kidney function.
Keywords: ddc:610